Application of space syntax in neighbourhood park research: an investigation of multiple socio-spatial attributes of park use. Issue 4 (3rd April 2023) - Can Traunmüller, Işın; İnce Keller, İrem and Şenol, Fatma
ABSTRACT: This case study investigates the actual park use as determined by the socio-spatial attributes of neighbourhoods and parks. As a contribution to the research about park accessibility, it integrates the space syntax analysis with the observation-based fieldwork data about the attributes of neighbourhoods, parks, and park users in 42 parks of 2 adjacent neighbourhoods in Izmir City (Turkey). With its syntactic measures (connectivity, integration, and choice), the study analysis describes the street configuration around these neighbourhood parks. Also, 3 multiple regression analyses are deployed to examine how the syntactic data along with the other neighbourhood and park attributes affect the number of users observed in 42 parks. The study contributes to the research about space syntax tools for analysing the organisational logic of parks in the neighbourhoods while also integrating other socio-spatial attributes of parks.